2023
DOI: 10.3390/jcm12175501
|View full text |Cite
|
Sign up to set email alerts
|

Advances in the Relationship between Respiratory Viruses and Asthma

Sergio Romero-Tapia,
Crystell Guzmán Priego,
Blanca Del-Río-Navarro
et al.

Abstract: Several studies have reported that viral infection is closely associated with the onset, progression, and exacerbation of asthma. The purpose of this review is to summarize the role that viral infections have in the pathogenesis of asthma onset and exacerbations, as well as discuss interrelated protective and risk factors of asthma and current treatment options. Furthermore, we present current knowledge of the innate immunological pathways driving host defense, including changes in the epithelial barrier. In a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 102 publications
0
2
0
Order By: Relevance
“…56 It is to be noted that these clinical conditions usually follow acute viral RIs in children. 57 Therefore, this literature evidences confirmed that these products could effectively and safely prevent RRIs.…”
Section: Intergroup Analysismentioning
confidence: 58%
“…56 It is to be noted that these clinical conditions usually follow acute viral RIs in children. 57 Therefore, this literature evidences confirmed that these products could effectively and safely prevent RRIs.…”
Section: Intergroup Analysismentioning
confidence: 58%
“…A recent study indicated that the approximately 15%of 5-year current asthma cases could be prevented by avoiding RSV infection during infancy 21 . Additionally, recurrent infections with other viruses, such as rhinovirus, in uenza virus, adenovirus, and can lead to the occurrence of asthma 22 . For the infection of the novel coronavirus, the initial focus has been on Long COVID syndrome.…”
Section: Resultsmentioning
confidence: 99%